The form (fa`ala), its structures and meanings in the morphological Studies - Ibrahim Mohammed, Lect. Dr. Abdul Hussein (Basra studies journal, 2026)
The ancient linguists, especially the morphologists, divided the simple trilateral verb forms into three categories: (fa`ula) with a (damma) on the first letter, (fa`ila) with a (kasra) on the first letter, and (fa`ala) with a (fatha) on the first letter. It is noted that the first formula, which has a (damma) on the first letter, does not have a present tense except with a (damma) on the first letter, the second formula, which has a (kasra) on the first letter, does not have a present tense except with a (kasra) or a (fatha) on the first letter, and the third formula, which has a (fatha) on the first letter, does not have a present tense except with a (damma), (kasras), or a (fatha) on the first letter. The third form is one of the most frequently used verbal forms in the speech of the Arabs and the most abundant in meanings. It is almost impossible to mention a meaning without some of its verbs including overcoming, gathering, separating, giving, preventing, rejecting, overcoming, repelling, repelling, harming, settling, covering up, etc. The form fa’ala, with all its forms and the other forms converted to it, constitutes a system of morphological meanings that no other form can accommodate. This study is an attempt to examine this form, clarify the characteristics of the verbs included under it, and explain the general morphological meanings that are revealed through its verbs. The research is divided into an introduction to abstract morphological forms and two sections. Firstly, the study presented the rules or characteristics of the verbs that belong to this form, noting the rules for each section separately. In the second section, the study explained the most common morphological meanings that can be found for this form, regardless of the vowel of the verb’s ’ayn in the present tense